Constraint-Based Simulation of Biological Systems Described by Molecular Interaction Maps - Bortolussi, L.; Fonda, S.; Policriti, A. (2007 IEEE International Conference on Bioinformatics and Biomedicine (BIBM 2007), 2007)
We present a method to simulate biochemical networks described by the graphical notation of Molecular Interaction Maps within stochastic Concurrent Constraint Programming. Such maps are compact, as they represent implicitly a wide set of reactions, and therefore not easy to simulate with standard tools. The encoding we propose is capable to stochastically simulate these maps implicitly, without generating the full list of reactions.